Economic valuation of integrated solid waste management in Kota Bharu, Kelantan - Nik Ab Rahim, Nik Nor Rahimah (2013)
Solid waste management in Kota Bharu is under responsibility of local authority,known as, Majlis Perbandaran Kota Bharu (MPKB). Solid waste management is a critical issue in Kota Bharu due to amalgamation of dwindling financial resources and population growth. These situations result in incompetency in controlling and handling excessive solid waste generation, giving rise to adverse effects on environment and public health. Introducing a new policy approach, integrated solid waste management can help to enhance condition of solid waste management in terms of reducing the waste generated, efficient services and sanitary waste disposal in Kota Bharu. The objective of this study was to determine economic value of integrated solid waste management in Kota Bharu, Kelantan. Choice modelling method was used to determine the communities’ preferences for services in integrated solid waste management and their willingness to pay for these services. A total of 300 respondents were interviewed face-to-face for data collection, representing the communities in Kota Bharu. Multinomial logit models were defined to analyze the collected data. The results implied that the communities agreed with integrated solid waste management by inclusion of implementation of waste segregation, provision of adequate waste container, regularity in waste collection and execution of sanitary landfill waste disposal. In measuring their willingness to pay, the marginal value for each service in integrated solid waste management was positive. It indicated their willingness to pay for services in integrated solid waste management. The results of this study can be helpful for policy makers and authorities in their decision-making for solid waste management improvement. The suggestion for integrated solid waste management in this study is coherent with enacted Act 672 to promote waste reduction, implement waste recovery and enhanced waste disposal. Therefore, the encouraging results can aid the authorities’ interventions for introducing integrated solid waste management in Kota Bharu, Kelantan.